BENTUK PENYAJIAN TARI GALOMBANG SANGGAR PITUAH BUNDODI KOTA PAYAKUMBUH - Anggraini , Hasnah; Mansyur, Herlinda (Universitas Negeri Padang, 2025)
This study aims to reveal, describe and analyse the Presentation Form of the Galombang Dance by Sanggar Pituah Bundo in Payakumbuh City at wedding celebrations. This type of research uses a qualitative approach with a descriptive analytical method. The main research instrument is the researcher themselves, who assisted with stationery, a camera and a mobile phone. Data collection techniques include literature study, observation, interviews, and documentation. Data analysis was conducted through data collection, data reduction, data presentation, drawing conclusions, and verification. The results of the study show that the Galombang Dance by Sanggar Pituah Bundo is a creative dance performed as a guest welcoming dance at wedding celebrations. The presentation form consists of 7 elements: movement, costume, music, dancers, props, dance type, and synopsis. The Galombang Dance movements are based on silat movements that have been modified and varied by the choreographer (Hendri) and consist of 6 main movements, namely the sambah pambuka movement, the panyambuik movement, the manyongsong movement, the pangaba movement, the manyongsong basamo movement, and the maarak ka palaminan movement. The costumes worn are characteristic of Minangkabau traditional attire, such as deta, teluk balango shirt, sisampiang, waist belt, and sarawa for the dancers, spear bearers, and flag bearers. The carano bearer wears the penghulu attire, consisting of bakaruik deta, loose black shirt, sisampiang, cawek, salempang, and sarawa gadang. The musicians wear harimau deta, sisampiang, and demang shirt. The music accompanying the Galombang Dance is performed by four men consisting of talempong pacik, gandang tambua, bansi, and pupuik serunai. The Galombang Dance dancers are eight men. The props used to complement the Galombang Dance performance are carried by four men and consist of carano, gubalo spears, and flag umbrellas. This type of dance is a pure type of dance whose presentation is non-representative.